Essential University Physics: Volume 1 (4th Edition) Clone

Published by Pearson
ISBN 10: 0-134-98855-8
ISBN 13: 978-0-13498-855-9

Chapter 10 - Section 10.3 - Rotational Inertia and the Analog of Newton’s Law - Example - Page 184: 10.9


$ a = \frac{ mg} {\frac{1}{2}M+m}$

Work Step by Step

We know the following equations: $ma = mg +( -T) = mg - \frac{1}{2}Ma $ $ I = \frac{1}{2} MR^2 $ $T = \frac{1}{2}Ma$ Solving the first equation for $a$ and combining these, we find: $ a = \frac{ mg} {\frac{1}{2}M+m}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.